(untitled) (Pedagogy of Higher and Secondary Education, 1999)
The article is devoted to intégral processes didactic interaction of teachers and pupils. The leading inner corrélation of given processesunity and integrity of intellectual and emotional relations of teacher and pupils and contents of éducation are investigated in it. Conclusions for teachers’ training for didactic interaction with pupils have been drawn.